Perspective on Fatima Mernissi's Position of Thought on Indonesian Women's Leadership in the 21st Century - Mujtahid Mujtahid; Ali Hasan Assidiqi; Dini Sadiyah (An-Nisa' Journal of Gender Studies, 2023)
There is no denying that the tradition of hadith thought is at the center of global debate. Of course, varied discourses will always arise in presenting the existence of hadith according to the context, including in the leadership of Indonesian women. The purpose of this study is to provide an overview of Mernissi's position and influence on the leadership thinking of Indonesian women in the 21st century. The method used is a type of literature research. The results showed that: 1) The origin of Fatima Mernissi's thought lies in her criticism of misogynistic hadiths that forbid women to be equal to men in being leaders. According to him, the hadith is not true because it has long been proven that women are able to compete fully, e.g. Aisha. 2) In the Indonesian context, Mernissi's idea is used as the basis of public figures that are always imitated by Indonesian women. Since Megawati became the first female president, many women have joined the government in the 21st century, including Sri Mulyani, Tri Rismaharini, and Khofifah. The data also showed an increase in women in parliament from 9% (2001-2004) to 20.5% (2019-2024).